(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2022)
The study thought deals with the contamination by biological oxygen demand and chemical oxygen demand from sewage waste of Gajraula. In this study area has no waste treatment system in Gajraula. This is condition among of cities in Uttar Pradesh. The untreated municipal waste water from this city is openly exhausted. There are no authorities for checking on polluting the ground water of this region. In nearly ninety percentages waste water formed worldwide remainder unprocessed creating extensive increased water contamination, particularly in rising countries. The current situation shows that the dealing of untreated waste water is essential if not the access of this waste water in underground water shall be extremely dangerous to flora and fauna of this region.